ANALYSIS OF THE INFLUENCE OF SUPPLY CHAIN PERFORMANCE & CONSUMER ASSESSMENTON THE COMPETITIVENESS OF MIE GACOAN MSMES - Edi Wahyu Wibowo; Muhamad Wildan H (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
To be successful in the competition, Mie Gacoan must be able to efficiently provide products to customers, with better service and quality in satisfying the needs of its customers, in meeting these needs the company must have good performance. Customers play a very important role in knowing how much the performance of the Mie Gacoan supply chain is in providing the Gacoan Spicy Mie that customers need where a smooth supply with good quality will produce good processed products if performance continues to be improved. This study was conducted with the aim of analyzing the Effect of Supply Chain Performance & Consumer Assessment on the Competitiveness of Mie Gacoan MSMEs. From the results of the t-test and F-test, it was found that Supply Chain & Assessment simultaneously and partially had a significant effect on the Competitiveness of Mie Gacoan. From the descriptive analysis of the Supply Chain obtained the lowest average score, namely the lowest average score of 4.39 which was in the statement that Mie Gacoan Products are famous for their very spicy Noodle menu compared to other MSMEs or restaurants. To improve the lowest score, Mie Gacoan can release innovations or the latest Spicy Noodle variants from the Mie Gacoan product, and provide other spicy flavor variants to consumers so that consumers are more interested in buying and using products from Mie Gacoan.